2012
DOI: 10.1039/c2lc40258k
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic very large scale integration (mVLSI) with integrated micromechanical valves

Abstract: Microfluidic chips with a high density of control elements are required to improve device performance parameters, such as throughput, sensitivity and dynamic range. In order to realize robust and accessible high-density microfluidic chips, we have fabricated a monolithic PDMS valve architecture with three layers, replacing the commonly used two-layer design. The design is realized through multi-layer soft lithography techniques, making it low cost and easy to fabricate. By carefully determining the process con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 22 publications
1
139
0
Order By: Relevance
“…The most widely recognized microvalve technologies are elastomeric valves based on multilayer soft lithography, developed at Stanford University [1], and monolithic membrane valves developed at the University of California Berkeley [4]. Although the software platform that we are developing is technology independent, we target the University of California Berkeley monolithic membrane valves, shown in Figure 1.…”
Section: Technology Overviewmentioning
confidence: 99%
“…The most widely recognized microvalve technologies are elastomeric valves based on multilayer soft lithography, developed at Stanford University [1], and monolithic membrane valves developed at the University of California Berkeley [4]. Although the software platform that we are developing is technology independent, we target the University of California Berkeley monolithic membrane valves, shown in Figure 1.…”
Section: Technology Overviewmentioning
confidence: 99%
“…The Quake research group at Stanford University has recently demonstrated integration of 1 million control elements onto a single chip is possible through microfluidic very large scale integration (mVLSI) [33 ]. mVLSI has the potential to realize high dynamic range and reconfigurable chips for digital-PCR, digital-MDA or digital-ELISA applications.…”
Section: Architectural Developmentsmentioning
confidence: 99%
“…Pressure actuated polydimethylsiloxane (PDMS) microvalves 3 deserve particular attention because, owing to their simplicity, thousands of units can be integrated on a single device, linking microfluidics and microelectronics 4 . PDMS valves currently represent an important tool for biology research [5][6][7][8] . In addition, dropletbased technology offers new methods of fluid manipulation, which are particularly powerful when high throughput is required [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%